The study of Guidelines on the application of Geographic Information Systems for finding routes to rescue victims from aircraft accidents - Thana, Kriengkrai (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2023)
This research is the study of Geographic Information System (GIS) to apply the process of Geographic Information System as a guideline to find the most suitable route to rescue the victims of an aircraft accident. The researcher collects research data and academic writings related to the application of geographic information systems in various fields, including a collection of documents related to search and rescue both in the military and lifesaving activity by the government and private organizations through qualitative research. After that, the researcher analyzes the problems and the needs to help the victims in order to find a method to properly analyze the problem. Then, the model and technological analysis of the geographic information system is deliberated using network analysis and multi-criteria decision analysis until obtaining a model for using the data to prepare the area data as the first process. Next, change the map data to the coordinate system and use it to create the relational database. Hence, the data can be used to write a set of instructions to achieve the result of the guideline of the process model of the connected GIS technology in order to process the result as the pathway to find the safest and the fastest route to rescue the victims.